Health Information Seeking Behavior about COVID-19 among Young Adults in Surabaya, Indonesia - Ratih Pandu Mustikasari; Heidy Arviani (Journal of Peace, Development and Communication, 2021)
Living through COVID-19 pandemic is a big challenge for everyone. People are trying their best to survive in many ways, including finding the best information to deal with it. Seeking health information is one of the things that people do to prepare themselves better in encountering this situation. This information will enhance their knowledge and help them understand this situation. The diverse health information regarding COVID-19 that is available in various media certainly provides many choices. People’s behavior on accessing health information in media is varied one to another, depending on age, gender, education, income, culture, and marital status. This objective of this study was to determine seeking health information behavior about COVID-19 among young adults in Surabaya. The young adults’ characters were suitable with the current situation, where the information circulated quickly in new media. This type of research belongs to Health Communication scope. The method used was quantitative descriptive and involving 100 young adult respondents. The numbers get from Slovin formula, with 5% error rate. The study collected data with questionnaires via Google form. The result showed that respondents accessed COVID-19 information on various themes and they preferred in-depth information.